THE IMPLEMENTATION OF JUST A MINUTE (JAM) TECHNIQUE TO SCAFFOLD STUDENTS’ SPEAKING FLUENCY: A CASE STUDY - Alan Jaelani; Imanda Rizkatria Utami (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2020)
Fluency happens to be the main obstacle for EFL learners in mastering speaking. There are many ways to scaffold students’ speaking fluency; one of them is Just a Minute (JAM). JAM is an impromptu speech activity where the speaker is supposed to express their ideas on the given topic, within the duration of a minute, without hesitation and repetition. The purposes of this research are to describe the implementation of JAM, the impact of using JAM, and the students’ perception towards the use of JAM. Case study method was used in conducting the research. The qualitative data was obtained from observation, rubric, questionnaire, and interview. The participants of the research are nine students of XII Hotel Accommodation in SMKN 3 Bogor. The results of the research show that JAM can be well-implemented in English formal classroom, JAM has given positive impact in scaffolding students’ speaking fluency, and JAM has gained students’ positive perception towards its use. This study suggests the English teachers to try adapting JAM as a mean to help their students scaffold the speaking fluency.